IMPLEMENTASI MAQASHID SYARIAH DALAM ETIKA BISNIS: EVALUASI EMPIRIS PADA LINGKUNGAN BISNIS MODERN - Muhammad Al-Mustafa; Azharsyah Ibrahim (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
The dynamics of conventional business often lead to distribution crises and moral degradation due to the separation of ethics and market mechanisms. This study aims to explore the concepts of business ethics and distributive justice in Islamic economics, and to formulate an operational framework based on Maqasid Shariah as a solution to economic inequality. The study uses a qualitative approach that integrates philosophical epistemological analysis, a comparative study of Western thought (such as John Rawls, Robert Nozick, and Amartya Sen), and an empirical evaluation of modern business practices. The results of the study show that Islamic economics offers a middle ground that acknowledges private property rights, but limits them with distributive moral obligations through instruments such as zakat and the prohibition of riba. However, the empirical evaluation revealed significant challenges in the form of the hegemony of the capitalist system and the 'syariahisation' of products, which often only becomes a legal formality without eliminating its exploitative nature. Both theoretically and practically, the study recommends the need for a fundamental paradigm shift in business entities towards true ethical-philosophical compliance to achieve genuine social welfare.